Analyses of IGFBP2 DNA methylation and mRNA expression in visceral and subcutaneous adipose tissues of obese subjects. (April 2019) - Zhang, Xiuli; Gu, Harvest F.; Frystyk, Jan; Efendic, Suad; Brismar, Kerstin; Thorell, Anders
Abstract: Insulin-like growth factor binding-protein 2 (IGFBP-2) is secreted by differentiating white adipocytes. Clinical studies demonstrate that circulating IGFBP-2 levels associated inversely with body mass index (BMI) and insulin resistance. To explore possible epigenetic changes of the IGFBP2 gene in obesity, we analyzed DNA methylation and mRNA expression in adipocytes from different depots. Healthy lean controls (BMI = 24.5 ± 0.3 kg/m 2, n = 19) and obese subjects (BMI > 35 kg/m 2, n = 24) were recruited. All subjects were Swedish Caucasian. Visceral abdominal adipose tissue (VAT) and subcutaneous adipose tissue (SAT) fragments were homogenized. Genomic DNA and total RNAs were extracted. Four CpG sites in the IGFBP2 gene promoter region were analyzed with bisulfite pyrosequencing. IGFBP2 gene expression at mRNA levels was determined with TaqMan real time RT-PCR. Serum samples were used for measurement of circulating IGFBP-2 and leptin levels. IGFBP2 DNA methylation levels in VAT were increased in obese subjects compared with controls ( P < .05). By contrast, IGFBP2 mRNA expression levels in VAT were lower in obesity subjects than in controls ( P < .05). In SAT, IGFBP2 DNA methylation and RNA expression levels were lower than in VAT, irrespective of obesity. Obese subjects demonstrated increased serum leptin levels ( P < .001) and reduced serum IGFBP-2 levels compared to controls ( P < .05). In conclusion, the current study demonstrates that IGFBP2 DNA methylation levels are increased in VAT from obese subjects. This suggests that IGFBP-2 is epigenetically regulated in abdominal obesity. Highlights: IGFBP-2 is secreted by differentiating white adipocytes. Clinical studies demonstrate that circulating IGFBP-2 levels associated inversely with BMI and insulin resistance. IGFBP2 DNA methylation levels in visceral abdominal adipose tissue were increased in obese subjects compared with lean controls, while IGFBP2 mRNA expression levels in the fat tissues were lower in obese subjects than in lean controls. Obese subjects demonstrated increased serum leptin levels and reduced serum IGFBP-2 levels compared to lean controls. This study demonstrates that IGFBP2 DNA methylation levels are increased in VAT from obese subjects and suggests that IGFBP-2 is epigenetically regulated in abdominal obesity.